STUDI AWAL POTENSI KOMPOSIT SELULOSE BAKTERIA-POLIANILIN SEBAGAI SUBSTRAT SEL SURYA - Dini Cahyandari; Ahmad Solichan; Toni Prasetyo (Universitas Muhammadiyah Semarang, 2014)
In recent decades, alternative energy from solar cell was investigating by many researcher because it can use as energy substitutes petrol and reduces green house effects. Nowdays, reduces petrol subsidized effect on increased prices of petrol. That is the reason why study on solar cell is important. Dye sensitized solar cell is one of simple technology to use solar energy became electricity. Polyanilin is one of polimer that is electricity conductor. Bacteria cellulose can use as template of polyanilin to polymerisation. SEM and FT-IR investigation shows that composites of bacterial cellulose-polyanilin polimerisation well on bacterial cellulose fiber that sintesized from nata de cassava.